2017
DOI: 10.1002/phar.2023
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Guidance for Antibiotic Dosing in Obese Adults

Abstract: Physiologic alterations seen in obesity commonly impact the pharmacokinetics (PK) and pharmacodynamics (PD) of antibiotics and may result in suboptimal dosing in this expanding but understudied population. Much of the published clinical and PK evidence to date consists of small patient populations and are retrospective with, not infrequently, heterogeneous results that in some cases are contradictory. In the last 10 years, additional antimicrobial PK/PD and clinical data encompassing prolonged infusion strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 75 publications
2
96
0
16
Order By: Relevance
“…Recent guidelines by Meng et al . favour Bayesian forecasting over the traditional trough measurements in adult obese patients …”
Section: Introductionmentioning
confidence: 99%
“…Recent guidelines by Meng et al . favour Bayesian forecasting over the traditional trough measurements in adult obese patients …”
Section: Introductionmentioning
confidence: 99%
“…Obese patients are another population where under-dosing may occur if dose adjustments are not implemented. A recent review of literature concluded that 23/34 (68%) of antibiotics were recommended for obesity-specific dosing (Meng et al, 2017). These problems may be further unknowingly amplified by the disposal of a residual volume of antibiotic within the administration set.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adequate antibiotic therapy with sufficient effective concentrations is particularly important for obese patients. However, guideline recommendations for linezolid suggest weight-independent dosing [16]. The plasma volume does not differ between non-obese and obese patients nearly as much as the volume of soft tissue [17].…”
Section: Introductionmentioning
confidence: 99%